2017
DOI: 10.1186/s11671-017-1884-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Synthesis Temperature on Structure and Magnetic Properties of (La,Nd)0.7Sr0.3MnO3 Nanoparticles

Abstract: Two sets of Nd-doped La0.7Sr0.3MnO3 nanoparticles were synthesized via sol-gel method with further heat treatment at 1073 and 1573 K, respectively. Crystallographic and magnetic properties of obtained nanoparticles were studied, and the effect of synthesis conditions on these properties was investigated. According to X-ray data, all particles crystallized in the distorted perovskite structure. Magnetic parameters, such as saturation magnetization, coercivity, Curie temperature, and specific loss power, which i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 36 publications
(43 reference statements)
0
4
0
Order By: Relevance
“…La 0.7−x Nd x Sr 0.3 MnO 3 , x = 0 and x = 0.1) via the solgel method with further heat treatment at 800 °C and 1300 °C, respectively. The results have indicated that both crystallographic and magnetic parameters (M s /T c ) of the nanoparticles (synthesized at 1300 °C) have monotonously changed with the doping amount of Nd [54].…”
Section: Effects On Physicochemical and Magneticmentioning
confidence: 98%
“…La 0.7−x Nd x Sr 0.3 MnO 3 , x = 0 and x = 0.1) via the solgel method with further heat treatment at 800 °C and 1300 °C, respectively. The results have indicated that both crystallographic and magnetic parameters (M s /T c ) of the nanoparticles (synthesized at 1300 °C) have monotonously changed with the doping amount of Nd [54].…”
Section: Effects On Physicochemical and Magneticmentioning
confidence: 98%
“…are still intensively studied. Works focusing on various physical properties of the compounds, such as magnetoresistance (MR), crystal structure change, metal-insulator transition, specific heat, large magneto-caloric effect, and high electrical conductivity have been reported [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. These rare … (T MI ) of about 243 K. In case of T>T MI , the resisitivity as a function of temperature could be described by two different models, namely the variable range hopping (VRH) model or Arhenius model and the adiabatic small polaron hopping (ASPH) model but more in line with the second model (ASPH).…”
Section: Introduction mentioning
confidence: 99%
“…The Curie temperature of La 1−x Sr x MnO 3 strongly depends on the chemical composition: it displays a maximum at x ≈ 0.3 (T Cmax ≈ 370 K) and is quite sharply reduced as x deviates from 0.3 [9][10][11]. A smoother change of the Curie temperature can be reached by additional substitutions either in manganese sublattice [12,13], or in lanthanum sublattice [14,15]. Such substitutions are expected to ensure reliable and controllable shift of T C towards the range, which is necessary for hyperthermia treatment [16].…”
Section: Introductionmentioning
confidence: 99%